Edmund Rubbra symphonist - Black, Leo (Boydell & Brewer, 2008)
Leo Black, a pupil of Rubbra in the 1950s, presents a full-scale study of his symphonies (the first for fifteen years). A biographical sketch throws light on legends about the BBC and Rubbra; there are full programme notes on each symphony, with accounts of important non-symphonic works. The music of Edmund Rubbra (1901-1986) has been unjustly neglected - arguably because its wide-ranging nature makes it difficult to categorise. He is perhaps best known as a symphonist; his eleven symphonies covered a period of musical and political upheaval [1934 - 1980], the first four reflecting the uneasy later 1930s, with a second global conflict no longer avoidable. The immediately-post-war ones document new emotional depths and his conversion, while the final symphonies show a man still in search of peace and reconciliation, overlooked by the world but certain he was on the right path. Leo Black, a pupil of Rubbra at Oxford in the 1950s, here presents a sympathetic full-scale study of these works (the first for some fifteen years). A succinct biographical sketch throws light on legends about the BBC and Rubbra; there are full programme notes on each symphony, with shorter accounts of important non-symphonic works, in particular a 'triptych' of concertos from the 1950s and major liturgical pieces composed around the time of the Second Vatican Council, after Rubbra's conversion to Catholicism. He also deals with the vexed question of Rubbra's mysticism. LEO BLACK is a former BBC chief producer for music and author of the highly-acclaimed Franz Schubert: Music and Belief [2003]